Letter from World University Service on Status of Refugee Hungarian Students. 56/57 - General - 627 7.XII.56. - 185 - Héderváry, Claire de (1956)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): World University Service Letter from World University Service to UN provides brief update on the status of refugee Hungarian students.